The Oxford Handbook of Ergativity 2017
DOI: 10.1093/oxfordhb/9780198739371.013.10
|View full text |Cite
|
Sign up to set email alerts
|

Split Ergativity is not about Ergativity

Abstract: This chapter argues that split ergativity is epiphenomenal, and that the factors which trigger its appearance are not limited to ergative systems in the first place. In both aspectual and person splits, the split is the result of a bifurcation of the clause into two distinct case/agreement domains, which renders the clause structurally intransitive. Since intransitive subjects do not appear with ergative marking, this straightforwardly accounts for the absence of ergative morphology. Crucially, such bifurcatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(8 citation statements)
references
References 388 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…The big question, then, is how to account for the fact that AK, like most varieties of Kurmanji, is a split ‐ergative language, not a uniformly ergative language, such that (13a) applies in past clauses but not in present clauses. Recent work on split ergativity has shown that splits can be attributed to phase‐theory domains (Baker , Coon & Preminger ): in order for dependent case (here ergative) to be assigned, NP1 and NP2 must be in the same spellout domain, in accordance with Chomsky's Phase Impenetrability Condition. When they are in different spellout domains, one NP is not visible to the other, and dependent case is not assigned.…”
Section: Background: Split‐ergative Case Marking In Akmentioning
confidence: 97%
See 2 more Smart Citations
“…The big question, then, is how to account for the fact that AK, like most varieties of Kurmanji, is a split ‐ergative language, not a uniformly ergative language, such that (13a) applies in past clauses but not in present clauses. Recent work on split ergativity has shown that splits can be attributed to phase‐theory domains (Baker , Coon & Preminger ): in order for dependent case (here ergative) to be assigned, NP1 and NP2 must be in the same spellout domain, in accordance with Chomsky's Phase Impenetrability Condition. When they are in different spellout domains, one NP is not visible to the other, and dependent case is not assigned.…”
Section: Background: Split‐ergative Case Marking In Akmentioning
confidence: 97%
“…What more precisely is the variable phase head that gives this result? For Coon & Preminger (), aspect is the crucial factor. Imperfective aspect splits the clause into two case domains, resulting in the absence of dependent‐case assignment.…”
Section: Background: Split‐ergative Case Marking In Akmentioning
confidence: 99%
See 1 more Smart Citation
“…Stem formants and split ergativity One final argument for a nominalization analysis of stem formants is that it brings Georgian split ergativity in line with analyses of Basque (Laka, 2006) and Chol (Coon and Preminger, 2015), which treat split ergativity as the result of a biclausal structure created by a nominal domain below the subject. As with Georgian, non-perfect tenses and aspects require extra structure and do not assign ergative case to their subjects.…”
Section: The Stem Formant As Nominalizermentioning
confidence: 99%
“…As with Georgian, non-perfect tenses and aspects require extra structure and do not assign ergative case to their subjects. This split based on the restriction that "in order to appear as a complement to a nonperfective aspect marker, a stem must be nominalized" (Coon and Preminger, 2015). Although much more work is necessary, this restriction is intuitively appropriate for the move from 'linear' and 'punctual' aspect in ProtoGeorgian, to the more diverse aspects available in Modern Georgian, as the addition of the feature [+collective] could allow an Aspect head to pick out sets of sub-events within the collection.…”
Section: The Stem Formant As Nominalizermentioning
confidence: 99%